(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2024)
Cooperatives face the challenge of improving operational efficiency and competitiveness in the increasingly advanced digital era. This research aims to develop and implement a digital management system to optimize the operations of the Agro Sejahtera Bersama Consumer Cooperative, which currently still uses traditional methods. The proposed system includes the digitization of transaction recording, inventory management, and financial reporting through a web-based platform, allowing real-time monitoring of transactions and inventory. The system development follows the software development lifecycle approach and uses modern web technology that is easily accessible. We conducted the evaluation by analyzing the cooperative’s performance before and after the system’s implementation, and surveying cooperative members to gauge their levels of satisfaction, transparency, and accountability. The research results show that this digital management system is effective in reducing recording errors, speeding up decision-making, and improving overall operational efficiency. In addition, the implementation of this system contributes to the expansion of the cooperative’s marketing network and provides more significant economic benefits to its members. Higher transparency in financial and operational management has also proven to increase members’ trust in the cooperative. This research concludes that the digitization of management systems can foster sustainable growth in cooperatives, and other cooperatives seeking a digital transformation can replicate its implementation.